2013
DOI: 10.1111/ases.12047
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic total pelvic exenteration with en bloc lateral lymph node dissection after neoadjuvant chemoradiotherapy for advanced primary rectal cancer

Abstract: Total pelvic exenteration (TPE) may be the only procedure that can cure T4 rectal cancer that directly invades the urinary bladder or prostate. Here, we describe our experience of laparoscopic TPE with en bloc lateral lymph node dissection for advanced primary rectal cancer. A 62-year-old man diagnosed with advanced lower rectal cancer (T4bN0M0) underwent laparoscopic TPE with en bloc lateral lymph node dissection after neoadjuvant chemoradiotherapy. Ligation of the dorsal vein complex was performed under dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 11 publications
1
21
0
1
Order By: Relevance
“…The locally advanced and locally recurrent rectal cancers with invasion limited to the anterior pelvic organ are good candidates for laparoscopic pelvic exenteration as a free circumferential margin can be achieved easily [28] . The b-TME Collaborative has generated a consensus guideline suggesting certain contraindications for these resections [7] , which holds true for MIS also.…”
Section: Pelvic Exenterationmentioning
confidence: 99%
See 1 more Smart Citation
“…The locally advanced and locally recurrent rectal cancers with invasion limited to the anterior pelvic organ are good candidates for laparoscopic pelvic exenteration as a free circumferential margin can be achieved easily [28] . The b-TME Collaborative has generated a consensus guideline suggesting certain contraindications for these resections [7] , which holds true for MIS also.…”
Section: Pelvic Exenterationmentioning
confidence: 99%
“…Patients who underwent multiple laparotomies and predicted to have severe small bowel adhesion are precluded from having MIS [29] . Initial experience in laparoscopic pelvic exenteration was reported in few case reports and video vignette [28,30] . Akiyoshi et al [31] demonstrated an laparoscopic pelvic exenteration for locally recurrent rectal cancer and suggested that laparoscopic pelvic exenteration was a technically challenging procedure that requires a long operative time with benefits of a very clear view of the operative field, allowing precise dissection, less blood loss, and a smaller abdominal wound.…”
Section: Pelvic Exenterationmentioning
confidence: 99%
“…12 Cases of laparoscopic and robotic TPE for urologic or gynecologic malignancies have been reported, [7][8][9][10] and multiport laparoscopic TPE for advanced rectal cancer has been reported. 11 Many surgeons have attempted to reduce the number of ports in laparoscopic surgery. Reduced port surgery aims to reduce the size and number of ports for preserving the view afforded by the laparoscope, while making the surgery less invasive.…”
Section: Discussionmentioning
confidence: 99%
“…6 Cases of laparoscopic and robotic TPE for urologic or gynecologic malignancies have been reported, [7][8][9][10] and multiport laparoscopic TPE for advanced rectal cancer has been reported. 11 However, SILS plus 1 port (SILSþ1) TPE for advanced primary rectal cancer has not been examined. In this report, we describe the SILSþ1 TPE for advanced primary rectal cancer.…”
mentioning
confidence: 99%
“…Multi‐visceral resection for T4 colorectal cancer has acceptable morbidity and mortality rates and a fair long‐term prognosis 4. Recent reports suggest that minimally invasive techniques for multi‐visceral resection should help achieve adequate short‐term outcomes and improvements in quality of life 5, 6, 7. Here, we describe our experience of complete en bloc resection by anal‐preserving laparoscopic anterior pelvic exenteration in a patient with locally advanced rectosigmoid cancer with direct invasion of the urinary bladder.…”
Section: Introductionmentioning
confidence: 99%